Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Guru SMP Negeri 2 Babakancikao Purwakarta - Fikri Irfan Muhyidin Radiningrat; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Human Resources, especially teachers, have a very large influence and are considered the main key in improving the quality of schools and educational goals. However, there is still a lack of collaboration and cooperation between teachers and between teachers and education staff, and the high rate of absenteeism without obvious reasons is also a significant problem that affects the continuity of learning. The purpose of this study is to determine the influence of work environment and work discipline on teacher performance partially and simultaneously at SMP Negeri 2 Babakancikao Purwakarta. The research method used is a quantitative method with data collection techniques through observation, questionnaires and interviews. The sample used was 31 people (saturated sample). Data analysis using multiple linear regression data analyzer with the help of SPSS software version 26. The results of the study show that the work environment has no effect on teacher performance. Meanwhile, work discipline has an effect and is significant on employee performance. Simultaneous hypothesis testing shows that the work environment and work discipline together have a significant influence on teacher performance. This research has important implications for the development of management policies and practices in the educational environment. Good work discipline contributes positively to teacher performance and improves performance to achieve organizational goals..